COVALENT, a method for co-designing value exchange in community-centred design. Issue 4 (2nd October 2018) - Pahk, Yoonyee; Self, James; Baek, Joon Sang
Abstract: It is challenging to design for mutually beneficial relationships in a multi-actor service system when these actors have diverse and conflicting interests, and lack usable methods and tools that support the design process. This study introduces a novel method for co-designing value exchange (COVALENT). COVALENT integrates the value analysis model, co-design strategy and service design tools, to support the conceptualisation of reciprocal value exchanges based on the analysis of and matching between, stakeholders' needs and resources. Its perceived effectiveness was validated through application to the development of community business models in Ulsan, South Korea. This study contributes to the knowledge of co-design by providing a method for co-designing services that aim to achieve reciprocal value exchanges in the context of community-centred design and by discussing the effectiveness of that method as perceived by users.